Late Holocene relative sea‐level fluctuations and crustal mobility at Bataneh (Najirum) archaeological site, Persian Gulf, Iran. Issue 5 (6th April 2021) - Pourkerman, Majid; Marriner, Nick; Morhange, Christophe; Djamali, Morteza; Lahijani, Hamid; Amjadi, Sedighe; Vacchi, Matteo; Jelodar, Mohammad E.; Spada, Giorgio; Tofighian, Hossein; Beni, Abdolmajid N.
Abstract: The impacts of relative sea‐level (RSL) variations and crust mobility on the development of ancient harbours in the northern Persian Gulf are poorly understood. Many unanswered questions remain with regard to the main reasons for a shift in the location of the most important ancient harbours in the northern part of the Persian Gulf coastal since 50 BC. Furthermore, some important early Islamic harbours, such as Siraf, have ancient city quarters that are today below the present sea level. The aim of this study is to evaluate the relationship between halokinesis and RSL changes using geophysical models and multidisciplinary geoarchaeological methods at the ancient Sassanid–Islamic site of Bataneh (presently known as Najirum) located at the foothill of an active Darang salt diapir. The results reveal that after the mid‐Holocene highstand, RSL regression was not continuous. The studied facies have recorded three RSL oscillations. The oscillations are correlated with the eustatic sea‐level position. During the first lowstand, important Sassanid harbours shifted from Rishar to Apologus. The second lowstand is consistent with the transition of maritime trade from Apologus to Siraf, during the Abbasid dynasty. Uplift of the Bataneh coastal zone exposed the city to risks from flooding and fluvial debris flows. With a modification of the local watershed, runoff water originating from the salt anticlinal was controlled and used for the extraction of gypsum in evaporation ponds. The economic expansion of Siraf led to Bataneh being abandoned with a shift in trade to Kish Island.